COVID-19 and diabetes—Two giants colliding: From pathophysiology to management - Pelle, Maria Chiara; Zaffina, Isabella; Provenzano, Michele; Moirano, Giovenale; Arturi, Franco (Frontiers in Endocrinology, 2022)
Since December 2019 a new coronavirus, called SARS-CoV2, has spread around the world causing a pandemic. From the beginning, SARS-CoV2 put a strain on the health system, in fact several patients had severe forms of disease with the need for hospitalization due to respiratory failure. To contain the pandemic, the most used approach has been lockdown, to date social restrictions are reduced, thanks to the advent of vaccines and targeted therapies. However, fatal events still occur among people at high risk of serious infection, such as patients with concomitant diabetes. Different mechanisms have been proposed to explain the poor prognosis of patients with diabetes and Corona Virus Disease-19 (COVID-19), however the specific cause is unclear. It is now known that insulin resistance (IR), inflammation and cytokine storm are involved. Moreover, SARS-CoV2 uses Angiotensin converting enzyme 2(ACE2) receptor to entry into cells, this receptor is expressed on beta cells pancreatic and this appears to cause hyperglycemia in both diabetic and non-diabetic patients during infection. In this study we will try to explain the mechanisms underlying the poor prognosis and what may improve the outcome of diabetic patients.